The performance of conventional and fluorescence-based methods for occlusal caries detection: an in vivo study with histological validation - Diniz, Michele Baffi; Boldieri, Thalita [UNESP]; Rodrigues, Jonas de Almeida; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP]; Lussi, Adrian; Cordeiro, Rita de Cássia Loiola [UNESP] (Elsevier, 2012)
Background The authors conducted an in vivo study to determine clinical cutoffs for a laser fluorescence (LF) device, an LF pen and a fluorescence camera (FC), as well as to evaluate the clinical performance of these methods and conventional methods in detecting occlusal caries in permanent teeth by using the histologic gold standard for total validation of the sample. Methods One trained examiner assessed 105 occlusal surfaces by using the LF device, LF pen, FC, International Caries Detection and Assessment System (ICDAS) criteria and bitewing (BW) radiographic methods. After tooth extraction, the authors assessed the teeth histologically. They determined the optimal clinical cutoffs by means of receiver operating characteristic curve analysis. Results The specificities and sensitivities for enamel and dentin caries detection versus only dentin caries detection thresholds were 0.60 and 0.93 and 0.77 and 0.52 (ICDAS), 1.00 and 0.29 and 0.97 and 0.44 (BW radiography), 1.00 and 0.85 and 0.77 and 0.81 (LF device), 0.80 and 0.89 and 0.71 and 0.85 (LF pen) and 0.80 and 0.74 and 0.49 and 0.85 (FC), respectively. The accuracy values were higher for ICDAS, the LF device and the LF pen than they were for BW radiography and the FC. Conclusions The clinical cutoffs for sound teeth, enamel carious lesions and dentin carious lesions were, respectively, 0 through 4, 5 through 27 and 28 through 99 (LF device); 0 through 4, 5 through 32 and 33 through 99 (LF pen); and 0 through 1.2, 1.3 and 1.4 through 5.0 (FC). The ICDAS, the LF device and the LF pen demonstrated good performance in helping detect occlusal caries in vivo. The ICDAS did not seem to perform as well at the D3 threshold (histologic scores 3 and 4) as at the D1 threshold (histologic scores 1–4). BW radiography and the FC had the lowest performances in helping detect lesions at the D1 and D3 thresholds, respectively. Clinical Implications Occlusal caries detection should be based primarily on visual inspection. Fluorescence-based methods may be used to provide a second opinion in clinical practice.
Keywords: Occlusal caries; Caries detection; Visual examination; Radiography; Fluorescence; Clinical study; Permanent teeth